Media arts education : transforming education through multimodal cognition, holistic learning, and techno-embodiment - Olsen, Dain (New York : Routledge, 2025)
"This book introduces and explains the emergent and dynamic discipline of Media Arts Education. Through an examination of its theoretical principles, holistic pedagogy, adaptive instructional practices, and diverse creative capacities, it demonstrates how Media Arts Education can lead to a more student-centered, interdisciplinary, and effective educational model. Chapters combine academic research and practical examples to give an in-depth understanding of Media Arts Education as it exists within schools today, as well as its potentials for educational advancement. Author Dain Olsen provides an instructional framework for the discipline, including its history, research from cognitive and learning science, pedagogical principles, and examples of instructional practice. The book discusses how Media Arts Education promotes active, multimodal and inquiry-based learning, constructivist methodology, and transdisciplinary integrations. Media arts affords students the ability to construct and simulate anything imaginable, supporting their self-directed creative inquiry. Later chapters include examples of media arts educator practices with lesson descriptions, project sequences, and instructional narratives. The book argues that Media Arts Education can form a multimodal, interconnective, and adaptive educational system which is more empowering, engaging, flexible, and equitable for all students' academic success. This resource is an essential companion for Media Arts educators at all levels. As it covers integration across a variety of contexts, it will additionally benefit educators in the fields of visual arts, career technical education, media studies, computer science and STEM and STEAM education"--
An introduction to media arts education -- A media arts-infused world -- Media arts in education -- The biological foundations of learning -- Multomodal, embodied cognition -- Multomodal learning -- Multimodal production as embodied learning -- Holistic learning -- Media arts education theory: The societal techno-sensorimotor system -- Remedying the problems of traditional education -- Media arts education meta-framework: The techno-embodiment of education -- Multimedia design: Developing aesthetic empathy -- Yearbook: Developing school culture -- Embodying language through media arts.
Keywords: Media programs (Education) -- Study and teaching; Media literacy -- Study and teaching; Mass media and education; Educational technology; EDUCATION / General; EDUCATION / Reference